Fintech Revolution in the Financial Industry - Ivana Martinčević; Sandra Črnjević; Igor Klopotan (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
Today, businesses operate in a highly dynamic and highly volatile market that requires timely and accurate responses. It is precisely the modern and dynamic financial environment that puts many challenges in front of the business of the company, confronts them with the advancement of modern information and communication technologies, which also raises the need for many innovative financial solutions. Financial market creates the new term "FinTeh" that includes some of the significant areas such as Bitcoin and Blockchain technology that have been evaluated in the last 5 years. With mentioned technologies, novelty in the financial market are definitely so-called "Neobanks", banks without physical locations. It is for this reason that we can argue that these forms of new technologies are evolving over time, being embraced and incorporated into companies business processes to maximize the added-value and gain a competitive advantage on the market.
Keywords: O33; G23; 330; financial innovations; financial market; digitalization; Fintech; Bitcoin; Blockchain; Neobank